Uropathogenic Escherichia coli (UPEC) cause impairment of spermatogenesis by inducing programmed necrosis - Lu, Yongning; Justus Liebig University Giessen (My University, 2011)
Infection and inflammation of the male reproductive tract are main aetiological factors of infertility. Inflammatory infertility is often based on loss of germ cell function and number. Uropathogenic E. coli (UPEC) is a relevant pathogen in urogenital infections. The aim of this study was to explore the pathomechanism that lead to germ cell loss during E. coli infection. Thus as a first step an in vivo model of epididymo-orchitis was established in rat by injecting a relevant strain of UPEC into the vas deferens in close proximity to the epididymis. Mimicking an infection ascending from the urinary tract, in the testis UPEC bacteria were found exclusively in the interstitial space 7 days post infection. Tracer experiments revealed that the integrity of the blood-testis and blood epididymis barrier was intact 7 days post-infection indicating that evasion of bacteria occurs probably intracellularly. In the testis, UPEC infection resulted in impairment of spermatogenesis by germ cell loss, damage of testicular somatic cells, a decrease in sperm numbers and a significant increase in TUNEL (+) cells. To investigate potential mechanism of germ cell death, hall mark steps of apoptosis were investigated. Activation of caspase-8 (extrinsic apoptotic pathway), caspase-3/-6 (intrinsic apoptotic pathway), caspase-1 (pyroptosis pathway) and the presence of 180 bp DNA fragments, all of which serve as indicators of the classical apoptotic pathway, were not observed in infected testis. Notably, electron microscopical examination revealed degenerative features of Sertoli cells (SC) in UPEC infected testis. Subsequent investigations focused on in vitro responses of SC and peritubular cells (PTC). Using UPEC wild type and mutant strains, it was shown that only a-hemolysin (+) E. coli strains were able to induce cell death of SC and PTC, but not strains that were lacking this pore forming virulence factor. Subsequent experiments revealed that the caspase-dependent apoptotic pathway was not involved in demise of these cells. Instead nuclear translocation of apoptosis inducing factor (AIF), rapid depletion of ATP, peripheral chromatin aggregation and condensation of nuclei was observed in UPEC treated SC. In contrast, activation of calpain, excessive production of reactive oxygen species (ROS), a gradual decline in ATP levels and the homogenous condensation of nuclei were evident in UPEC induced PTC death. Furthermore, the passive release of high mobility group protein B1 (HMGB1), as an indication of the necrosis, was observed in SC, PTC and infected testis. In summary, the findings indicate that UPEC infection causes the induction of an organized self-destruction cascade termed programmed necrosis in the testis, which may ultimately be the major mechanism contributing to impairment of fertility.

Infektion und Entzündung des männlichen Reproduktionstraktes gehören zu den wesentlichen Ursachen männlicher Infertilität. Die eingeschränkte Fertilität beruht oftmals auf einem Verlust an Keimzellen. Ziel der vorliegenden Arbeit war es die Pathomechanismen zu untersuchen, die zum Keimzellverlust führen. Deshalb wurde zunächst ein in vivo Modell in der Ratte etabliert, bei dem eine aus dem Harntrakt aufsteigende Epididymo-Orchitis durch Inokulation von uropathogenen Escherichia coli in den Ductus deferens nahe dem Nebenhoden modellhaft nachempfunden wurde. Sieben Tage nach Infektion wurden UPEC Bakterien ausschließlich im Interstitium des Hodens gefunden, obwohl sowohl die Blut-Hoden-Schranks als auch die Blut-Nebenhoden-Schranke intakt waren, wie begleitende Tracerstudien ergeben haben. Darüberhinaus führte die UPEC Infektion im Hoden zu einer Beeinträchtigung der Spermatogenese durch Keimzellverlust ausgedrückt durch eine reduzierte Anzahl an Spermatozoen, einer Schädigung der somatischen Zellen, und einer deutlich erhöhten Anzahl an TUNEL (+) Zellen im infizierten Hoden. Die für einen Zelltod durch den klassischen Apoptosesignalweg charakteristische Aktivierung von Caspase-8 (extrinsischer apoptotischer Signalweg), Caspase-3/-6 (intrinsischer apoptotischer Signalweg) und Caspase-1 (Pyroptosis), sowie die Bildung von ca. 180 bp langen DNA Fragmenten konnten in infizierten Hoden jedoch nicht beobachtet werden. Degenerative Veränderungen von Sertoli Zellen (SC) in infizierten Hoden wurden elektronenmikroskopisch nachgewiesen. In vitro konnte mit Hilfe von UPEC Wildtyp und Mutanten gezeigt werden, dass ein Zelltod in SC und Peritubulär-Zellen (PTC) abhängig von der Expression des Poren-bildenden Virulenzfaktors a-Hämolysin (+) ist. Weitere Experimente konnten zeigen, dass der Caspase-abhängige Apoptose-Signalweg nicht für den Zelltod der SC und PTC verantwortlich ist. Hingegen konnte in infizierten SC eine Translokation von AIF (apoptosis inducing factor) in den Zellkern, eine schnelle Depletion von ATP, periphere Chromatinaggregation und nukleäre Kondensation beobachtet werden. In Gegensatz dazu fanden sich in UPEC infizierten PTC eine Aktivierung von Calpain, eine massive Produktion von ROS (reactive oxygen species), eine schrittweise Erniedrigung der ATP-Spiegel sowie eine homogene nukleare Kondensation als charakteristische Merkmale. In SC und PTC als auch im infizierten Hoden wurde eine passive Freisetzung des High-Mobility-Group-Protein B1 (HMGB1), einem Nekrosemarker, beobachtet. Zusammenfassend kann festgestellt werden, dass eine UPEC Infektion im Hoden zu einem Keimzellverlust durch einen organisierten Selbstzerstörungsprozess führt, der als programmierte Nekrose bezeichnet wird.
Uropathogenic Escherichia coli (UPEC) verursachen Wertminderungen der Spermatogenese durch fehlerträchtige programmierte Nekrose
Keywords: Uropathogenic Escherichia coli; spermatogenesis; infection; infertility; programmed cell death; ddc:610